Yellowstone. Season 5, part 2 [videorecording (DVD)] - Sheridan, Taylor; Linson, John (Paramount Home Entertainment, 2025)
Yellowstone follows the Dutton family, owners of the largest cattle ranch in the U.S., as they battle constant threats from neighboring landowners, an Indian reservation, and a growing town. In the conclusion to Season Five, the fight for the Dutton legacy intensifies, with Beth, Rip and Jamie caught in a dangerous power struggle. As betrayals and shifting alliances threaten to tear them apart, the family faces devastating decisions that could determine the future of their empire.